The correlation between levels of vitamin D (25(HD)D) and the occurrence of necrotizing enterocolitis (NEC) in preterm infants - Eko Sulistijono; Brigitta Ida Resita Vebrianti Corebima; Yesi Adisti Pramitasari (Pediatric Sciences Journal, 2023)
Introduction: One of the causes of gastrointestinal emergencies in newborns is necrotizing enterocolitis (NEC). A fetus is fully dependent on transfer from the mother as it lacks endogenous 25(OH)D production. Transplacental vitamin D transmission mainly occurs due to the elevated risk of vitamin D insufficiency in preterm newborns during the third trimester of pregnancy. This research is important to raise awareness about the importance of early initial screening of vitamin D levels in preterm infants in Indonesia. Methods: This study used an observational research design which is a cohort study, taking place during March–May 2020 in the neonatology inpatient ward of dr. Saiful Anwar General Hospital Malang. The enzyme-linked immunosorbent assay (ELISA) technique was used to measure the amount of vitamin D in the blood. The Kolmogorov-Smirnov test and the Levene test were used to determine whether the data were normal and homogeneous, respectively. Result: It was found that vitamin D levels in preterm infants with NEC were lower (10.18 ± 4.07 ng/mL) than in preterm infants without NEC (16.95 ± 4.45 ng/mL). The bivariate analysis result showed that vitamin D deficiency increased the risk of NEC by 10.7 times with p-value = 0.033 (95% CI 1.2-24.9). Furthermore, multivariate analysis found that vitamin D deficiency increased the occurrence of NEC by 19.4 times with a p-value = 0.043 (95%CI 0.7-21.7) and respiratory distress could increase the incidence of NEC by 9.4 times with a p-value =0.02 (95%CI 1.2-70). Conclusion: Vitamin D (25(OH)D) levels were lower in preterm infants with necrotizing enterocolitis compared to preterm infants without necrotizing enterocolitis. This study showed a significant correlation between vitamin D(25(OH)D) levels and the case of necrotizing enterocolitis in preterm infants.